Linguistic and Extralinguistic Aspects of Study of Modern Russian Rap Texts - E. V. Grudeva; A. A. Diveeva (Научный диалог, 2021)
An overview of modern domestic and foreign linguistic studies of rap texts is presented. The features of rap as part of the global hip-hop culture are considered. The proof is given that rap text as a component of rap culture is the dominant of the subculture, and domestic rap is an authentic phenomenon. It is shown that over the past twenty years, the subject of research in the field of studying Russian-language rap texts has become more diverse. The main linguistic aspects of the study of rap texts (lexicon of rappers, slangisms, intertextual inclusions, gender characteristics, paronymic attraction) are revealed. The novelty of the research is seen in the fact that the status of rap text as an object of linguistic research has been clarified, and guidelines have been created for further practical analysis of this type of text. For the first time, a number of works by foreign scientists that have not previously been presented in the domestic scientific space and which define new perspectives in the study of the Russian-language rap text are highlighted. Particular attention is paid to debatable issues about the status of rap text, its genre features. The authors of the article argue that the leading mechanism of text generation in Russian-language rap is paronymic attraction, which gives reason to consider rap text as a literary text.